Real-Time Embedded Systems: Open-Source Operating Systems Perspective - Bertolotti, Ivan Cibrario; Manduchi, Gabriele (Embedded systems, 2012)
This book gives readers a hands-on, working knowledge of real-time operating systems and how they can be applied in the embedded system domain. The authors assess various case studies, using them as running examples to reinforce introduction of theoretical material. They also discuss increasingly popular open-source operating systems. Helpful for average system designers that have no significant previous experience with real-time operating systems, this book's content will help readers understand the benefits and weaknesses of each. With this knowledge, they can decide whether or not to adopt it for a project, or rely on more traditional, but less powerful, techniques.